2022
DOI: 10.1007/s12144-021-02596-5
|View full text |Cite
|
Sign up to set email alerts
|

Individual and class-level factors for students’ management of homework environment: The self-regulation perspective

Abstract: The present study investigated the predictive effects of clusters of variables on homework environment management based on the data from 3018 students in Grade 8. These clusters included: background variables, homework characteristics, adult support and monitoring, homework purposes, goal orientations, and contextual control. At the individual level, management of homework environment was significantly related to at least one variable from each of the six clusters. Specifically, it was associated negatively wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 83 publications
(187 reference statements)
0
2
0
Order By: Relevance
“…Moreover, EG students, compared to CG students, reported higher skills to manage their homework time, and reduced deficits in self-regulation which are usually observed in traditional homework settings. In addition to increasing the amount of homework that would eventually be completed and possibly improving the quality of homework completion (Xu, 2022a), this provision for active environmental control would optimize the self-management effort involved in studying (Dent & Koenka, 2016;Gebauer et al, 2019) and would be conducive to learning by increasing the chances of concentration during homework (Lens et al, 2008;Pintrich, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, EG students, compared to CG students, reported higher skills to manage their homework time, and reduced deficits in self-regulation which are usually observed in traditional homework settings. In addition to increasing the amount of homework that would eventually be completed and possibly improving the quality of homework completion (Xu, 2022a), this provision for active environmental control would optimize the self-management effort involved in studying (Dent & Koenka, 2016;Gebauer et al, 2019) and would be conducive to learning by increasing the chances of concentration during homework (Lens et al, 2008;Pintrich, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that quality homework can positively influence the learner's behavior and achievement (Trautwein et al, 2002(Trautwein et al, , 2006Lüdtke, 2007, 2009;Dettmers et al, 2010;Rosário et al, 2018). Moreover, a student's motivation to complete homework is positively related to its perceived quality (Trautwein et al, 2006;Trautwein and Lüdtke, 2007;Rosário et al, 2018;Xu et al, 2021;Xu, 2022). For example, Rosário et al (2018) found that when students perceive their homework to be high quality, they try harder, complete homework more often, perform better on assignments, and get higher grades in mathematics.…”
Section: Homeworkmentioning
confidence: 98%